Extracellular DNA Impedes the Transport of Vancomycin in Staphylococcus epidermidis Biofilms Preexposed to Subinhibitory Concentrations of Vancomycin - Doroshenko, Natalya (Antimicrob Agents Chemother, 2014)
Staphylococcus epidermidis biofilm formation is responsible for the persistence of orthopedic implant infections. Previous studies have shown that exposure of S. epidermidis biofilms to sub-MICs of antibiotics induced an increased level of biofilm persistence. BODIPY FL-vancomycin (a fluorescent vancomycin conjugate) and confocal microscopy were used to show that the penetration of vancomycin through sub-MIC-vancomycin-treated S. epidermidis biofilms was impeded compared to that of control, untreated biofilms. Further experiments showed an increase in the extracellular DNA (eDNA) concentration in biofilms preexposed to sub-MIC vancomycin, suggesting a potential role for eDNA in the hindrance of vancomycin activity. Exogenously added, S. epidermidis DNA increased the planktonic vancomycin MIC and protected biofilm cells from lethal vancomycin concentrations. Finally, isothermal titration calorimetry (ITC) revealed that the binding constant of DNA and vancomycin was 100-fold higher than the previously reported binding constant of vancomycin and its intended cellular d-Ala-d-Ala peptide target. This study provides an explanation of the eDNA-based mechanism of antibiotic tolerance in sub-MIC-vancomycin-treated S. epidermidis biofilms, which might be an important factor for the persistence of biofilm infections.